2017
DOI: 10.1364/oe.25.007408
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced photochemical synthesis of branched Ag@Au bimetallic nanodendrites as a prominent substrate for surface-enhanced Raman scattering spectroscopy

Abstract: The project of wielding laser light as a versatile tool for sculpting branched Ag@Au bimetallic nanocrystals with mean size of ~50 nm has been developed in this work. The moderate overgrowth of Ag species with negligible damage effect on the branched Ag@Au nanostructures was achieved by laser-induced photo-oxidation. The final Ag@Au nanodendrites exhibit superior surface enhanced Raman scattering (SERS) activities with an enhancement factor up to ~1011 and a detection limit as low as ~10-14 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…The broad absorbance indicates the presence NPs with a wide size distribution by non-spherical shape, surface morphology and possible formation of nanoaggregates. Based on the previous reports, the absorption peak of bimetallic NPs shifted to a longer wavelength side due to the (i) concentration of precursor [32], (ii) irradiation energy, and (iii) time of exposure. Xu et al fabricated the bimetallic Ag@Au nanocrystals and observed the red shift in the SPR peak (∼858 nm) achieved using laser-induced photo-oxidation.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…The broad absorbance indicates the presence NPs with a wide size distribution by non-spherical shape, surface morphology and possible formation of nanoaggregates. Based on the previous reports, the absorption peak of bimetallic NPs shifted to a longer wavelength side due to the (i) concentration of precursor [32], (ii) irradiation energy, and (iii) time of exposure. Xu et al fabricated the bimetallic Ag@Au nanocrystals and observed the red shift in the SPR peak (∼858 nm) achieved using laser-induced photo-oxidation.…”
Section: Resultsmentioning
confidence: 83%
“…Furthermore, we have also reported the detection of 2, 4-Dinitrotoluene using Ag-Au nanostructures achieved using femtosecond laser ablation [13]. Recently, composite nanoparticles have attracted much attention by physicists, chemists and material scientists due to their higher catalytic, electronic, optical, physicochemical properties and multiple functionalities [2,[27][28][29][30][31][32][33][34]. To fabricate bimetallic/alloy NPs, there are several ways or (a) short pulse laser irradiation of colloidal mixture of NPs (b) ablation of a target in the presence of a precursor solution or (c) short pulse laser irradiation of alloy target in liquid media etc.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…For Ag-Cu alloy NPs 1.3 times higher EFs was noticed than the Ag NPs, could be ascribed to the electromagnetic coupling at the interface of Cu and Ag, which generates the superior localised EM eld and synergetic effect. 8,53 He et al fabricated Ag-Cu alloy NPs by galvanic replacement technique and shown the tailorable SERS and catalysis activity. 54 Hu et al reported the Ag-Cu SERS substrate act as a promising material for detection R6G (10 À13 M).…”
Section: Sers Activity Of Ag Cu and Ag-cu Npsmentioning
confidence: 99%
“…17 The experimental setup is similar to that described in our previous studies. [18][19][20] Briey, a well-polished Ag metal target (10 mm in diameter and 2 mm in thickness) was placed on the bottom of a glass dish rotating with speed of $300 rpm that was lled with 2.5 mm depth of liquid solution containing 0.2 M TAA and 8 mL distilled water. The TAA can provide the sulfur source for the construction of Ag 2 S materials.…”
Section: Methodsmentioning
confidence: 99%